Design and creativity policy, management and practice - aJulier, Guy.; aMoor, Liz. (Oxford New York Berg Publishers, 2009)
"Does the management of design conflict with traditional ideas of creative freedom and autonomy? How do government policies and business priorities influence the day-to-day practices of designers? And how far have the processes and purpose of creative work been changed by its new centrality to business and government? Bringing together case studies and material from a range of industries and contexts, as well as a series of interviews with practitioners, Design and Creativity provides a cutting-edge account of key trends in the creative industries at the start of the 21st century. Design and other creative industries shape our lives in numerous ways, providing 'cultural' goods such as films, music and magazines, but they also shape the look and feel of everyday objects and spaces. The creative industries are important economically; and governments and businesses now make considerable efforts to manage creativity for a range of political and economic ends"--Provided by publisher.
Introduction: design and creativity / Liz Moor and Guy Julier -- Design and policy. Designing the state / Liz Moor ; Designing the city / Guy Julier ; Design, innovation and policy at local level / Katie Hill and Guy Julier ; Public art, design-led regeneration and its evaluation / Doug Sandle ; Design client, patron and showcase : the museum and the creative industries / Jane Pavitt -- Managing design in context. Routinized labour in the graphic design studio / AnneMarie Dorland ; Auditing in communication design / Paul Springer ; Researchers in the world of product design / Nitzan Waisberg ; The turn to service design / Lucy Kimbell ; Cinema by design : Hollywood as a network neighbourhood / Damian Sutton ; Visual continuity and innovation in editorial design practice / Sarah Owens -- Interviews with practitioners. Kobus Mentz, Urbanism Plus ; Tim Allnutt, Clemmow Hornby Inge ; Jason Severs, Frog Design ; David Scothron, Product First ; Ben Reason, live\work ; Ilona To?rmikoski, Hahmo ; Peter Higgins, Land Design Studio ; Conclusion: counting creativity / Guy Julier and Liz Moor.
Keywords: Cultural industries -- Management; aCreative ability; aDesign